Earthquakes in Turkey and Syria in 2023 and geodynamics of the Caucasus-Anatolian region - V. B. Svalova (Известия высших учебных заведений: Геология и разведка, 2023)
Background. The intensification of natural disasters all over the world requires the development of new approaches to the study of geological processes. This particularly concerns the areas at the boundaries of lithospheric plates, which are characterized by earthquakes, increased seismicity, volcanism, intensive heat flows, geothermal manifestations, landslide processes, tsunamis, and other dangerous natural processes and hazards. The Caucasus-Anatolian-Arabian region is a complex highly-stressed geodynamic structure, characterized by an increased heat flow, seismicity, magmatism, and volcanism. The geodynamics of this region is determined by the collision of the Eurasian and Arabian lithosphere plates, as well as by the evolution of the Alpine-Himalayan belt and surrounding areas. A 7.8 magnitude earthquake hit the South-East Turkey and North-West Syria on February 6, 2023. This was the largest earthquake in Turkey since the 1939 Erzincan earthquake, and the second-strongest since the 1668 North Anatolia earthquake. More than 52,800 deaths were confirmed, with about 46,100 in Turkey and 6,700 in Syria. It is the deadliest natural disaster in Turkey’s modern history with the estimated damage of over $100 billion.   Aim. To construct geodynamic models for the deep structure of natural hazard regions, which can contribute to the study of active continental margins. This information is necessary for earthquake forecasting and prognosis, as well as for assessing geoecological risks and preparing the population in the event of natural disasters and catastrophes.   Materials and methods. The formation and evolution processes of geological structures in complex geodynamic settings, as well as the forecasting and prognosis of natural hazards, required an analysis of all available geological and geophysical data. The methods of mechanical and mathematical modeling were used to formulate and solve the research problems.   Results. Geodynamic models of the regions of hazardous natural processes were constructed with the purpose of forecasting and preventing natural disasters and catastrophes. An algorithm for creating monitoring systems was proposed.   Conclusion. In several years (1–10 years), another earthquake near Istanbul can be expected. In the case that no large earthquake occurs in the East Anatolian fault in 1–2 years, this event is likely to occur in 100 years only.